Stoma Reversal : A Restropective Study of 36 Cases at A Non-Government Hospital (IAHS Medical Journal, 2022)
Background : Formation of intestinal stoma is a common surgical practice. In this study, we aim to study the indications for stoma creation, complications of stomas, timing and methods of stoma reversal, reasons for any delays and post-reversal complications.Material and methods: This is a restropective study Charts of patients who underwent stoma creation and reversal over a 3 year period from January 2018 to December 2020 at Banghbandhu Memorial Hospital are included in this study.Results: A total of 49stomas were created out of which 36 were reversed. Overall pre-takedown complications were 26 % and post-takedown complications were 30% most of which were minor complications, not requiring major interventions. There was no significant difference in outcome due to early vs. late reversal, types of anesthesia or reversal technique.Conclusion: Reversal of temporary stomas can be done safely at an early date, with no demand of special anesthesia, requiring minimal access to the abdomen and with safe early discharge without expecting serious complications or readmissions.IAHS Medical Journal Vol 5(1), June 2022; 78-81